2022
DOI: 10.1109/tits.2021.3127944
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Driver Sleepiness Using Consumer Wearable Devices in Manual and Partial Automated Real-Road Driving

Abstract: Driver sleepiness constitutes a well-known traffic safety risk. With the introduction of automated driving systems, the chance of getting sleepy and even falling asleep at wheel could increase further. Conventional sleepiness detection methods based on driving performance and behavior may not be available under automated driving. Methods based on physiological measurements such as heart rate variability (HRV) becomes a potential solution under automated driving. However, with reduced task load, HRV could poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…The answer to the question of whether automation does or does not lead to driver fatigue hinges on the follow-up question: compared to what? Compared to a strong experimental control, these data suggest that automation may not lead to levels of fatigue suggested by online videos and some prior research (ABC, 2023 ; Vogelpohl et al, 2019 ; Lu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 41%
“…The answer to the question of whether automation does or does not lead to driver fatigue hinges on the follow-up question: compared to what? Compared to a strong experimental control, these data suggest that automation may not lead to levels of fatigue suggested by online videos and some prior research (ABC, 2023 ; Vogelpohl et al, 2019 ; Lu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 41%
“…Based on the results of this research, a comparison can be made with previous research that created a prototype in the form of a belt [7]. This research utilized different components, specifically the U-Blox Neo 6M GPS for reading position and the MLX90614 sensor for measuring the temperature of children with Autism Spectrum Disorder (ASD).…”
Section: Comparison Of Drowsiness Detection Resultsmentioning
confidence: 99%
“…Research [6] detects driver drowsiness using a visual-based approach, and driving behavior features do not mention the sample size used in this study, making it difficult to assess the accuracy and generalizability of the study results. Furthermore, research [7] identified driver drowsiness using consumer wearable devices in partially automated driving on real roads. This study shows that partially automated driving has little impact on the relationship between heart rate variability (HRV) and sleepiness, and commercial wearable heart rate monitors have the potential to be a useful tool for assessing driver sleepiness during manual and partially automated driving.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between HRV and drowsiness was examined using consumer wearable devices i.e., Garmin brand sports watches and Polar H10 chest bands for recording RR intervals. Drowsy drivers for both manual and partially automated driving showed lower HR, increased HF, LF power and LF/HF [65] In addition, relationship between HRV and the KSS is not influenced by different pre-processing techniques for outlier heartbeat removal, spectrum transformation of HRV data [64].…”
Section: Driver Drowsinessmentioning
confidence: 91%